(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2026)
The study investigated the subsurface tectonic framework and structural disposition of the basement/sedimentary transition zone in the southeastern part of Bauchi, Northeastern Nigeria, to delineate the basal and lateral contacts and unravel some of the hydrogeolog ical and engineering challenges in such areas. The method deployed involved the analysis of high-resolution aeromagnetic data, through the application of several filtering tech niques. The transformation techniques applied include reduction to pole, second vertical derivative techniques using analytical signal, and Euler deconvolution. The Euler depth result range of 1–200 m coincides with the region where basement rocks outcrop on the surface, while the depth range between 0 and −800 m corresponds to the sedimentary terrain (the Kerri-Kerri formation) or part of the area where the basement rocks are over lain by thick overburden sediments. The 2-D depth model around the transition zone showed high variability as it ranged from 0 to −500 m owing to the presence of basement highs and depressions. The basement highs are usually characterized by impermeable rocks with poor aquifer characteristics and are responsible for the failure of boreholes in these zones. The basement depressions, however, constitute good groundwater prospects depending on the hydrological properties of the sedimentary infill. The general orienta tion of lineaments in the area revealed NW–SE, NE–SW, and ENE–WSW, with minor N–S and E–W trends, suggesting a pan-African origin. The occurrence of lineaments in parts of the contact zones also contributes to the groundwater prospects. The erratic bedrock relief exhibited by the study area is also detrimental to the foundation of pavement struc tures as it undermines their durability. Therefore, a detailed site investigation is crucial in such geological contact zones prior to the erection of structures. Additionally, vertical electrical soundings are recommended before borehole drilling to ascertain the suitability of these hydrogeological complex zones.